PENGEMBANGAN MEDIA DAM-DAMAN DALAM MATA PELAJARAN FIQIH MATERI HAJI KELAS V MI AL MUSLIMIYAH RANDUBLATUNG BLORA - M, Hesti Puspitasari; Husna, M. Ahsanul; Ulummudin, Imam Khoirul (At-Tuhfah : Jurnal Studi Keislaman, 2021)
Daman-Daman are one of the traditional games in Central Java, the game is like chess but there is no check math but eating or eating. Furthermore, the researcher developed this game into a Fiqh learning Hajj Material in the class V at MI Al Muslimiyah, Randublatung District, Blora Regency. This type of research is Research and Development (RnD). The method used to analyze data with quantitative descriptive analysis techniques. The learning media development model used is the ADDIE model, which has 5 stages and in this study it is simplified into 3 stages, namely ADD. The results of this development research are as follows: a) By the material expert covering the Learning Aspect got a percentage of 86.6% in the very good category, the Content Aspect got a percentage of 92% in the very good category, the Evaluation Aspect got a percentage of 84% with the very good category, b) By Media Experts covering Display Aspects got a percentage of 86% with a very good category, Usage Aspects got a percentage of 80% with a good category, c) The trial results got a mean rating of 4.25 with a very good assessment.